SISTEM INFORMASI PEMESANAN PRODUK FORNITURE BERBASIS WEB - siti winarsih (Jurnal Ilmiah Sistem Informasi, 2022)
In the modern era, the development of computers and technology makes everything have to be fast, as well as communication techniques, grow very rapidly. Communication can be defined as the process of displaying, changing, interpreting, or processing information between humans or machines. Data communication has become a basic requirement in the business world where they provide information to each other via the computer where they are located. The Internet is a network solution that can connect several local networks in an area, city or even a country. With the internet we can connect several local networks in every place. Not only that, with internet facilities, everyone can carry out any activity such as sending Emails, searching for data, playing games, accessing banks, or even shopping at on-line shops between countries. The Word Wide Web (www) is a part of the internet that is very well known in the internet world, with the www a user can display a virtual page called a Web site. CAHAYA SAKTI MULTI INTRACO Semarang is a distributor company engaged in the Olympic brand furniture business. In its development, the company still needs an information technology, especially in presenting information on ordering furniture products.